Transient Unilateral Recurrent Laryngeal Nerve Palsy Presenting as Post-extubation Stridor after Total Thyroidectomy for Non-toxic Multinodular Goiter: Anesthetic Implications and Airway Rescue - Muhammad Rezha Mansyur; Isngadi; Jeffri Prasetyo Utomo (Open Access Indonesian Journal of Medical Reviews, 2026)
Total thyroidectomy is among the most frequently performed endocrine procedures worldwide, yet it carries a defined risk of recurrent laryngeal nerve (RLN) injury that can precipitate post-extubation stridor and emergent airway compromise. Transient unilateral RLN palsy is estimated to occur in 2 to 10 percent of cases for benign disease and remains an important anesthetic consideration even in carefully planned surgery. We report the case of a 53-year-old woman with controlled hypertension and a longstanding bilateral non-toxic multinodular goiter of 8.5 by 10 centimeters who underwent intraoperative conversion from subtotal to total thyroidectomy under general anesthesia with endotracheal intubation. Intraoperative course was stable on a balanced regimen of midazolam, fentanyl, propofol, atracurium, and isoflurane. Ten minutes after a smooth extubation, she developed inspiratory stridor, suprasternal retractions, and desaturation. Awake reintubation with preserved spontaneous ventilation was performed using low-dose sedation, intravenous lidocaine, and direct laryngoscopy, which simultaneously secured the airway and demonstrated paresis of the left vocal cord while the right cord was mobile. The patient was transferred to the intensive care unit, received systemic methylprednisolone, and was extubated successfully within 24 hours with complete recovery of bilateral vocal cord mobility on follow-up laryngoscopy. In conclusion, awake reintubation with maintained spontaneous breathing is a powerful maneuver that secures the airway and confirms the laryngeal diagnosis at a single procedure. Early systemic corticosteroid, vigilant monitoring, and otolaryngology liaison support rapid neurapraxia recovery, with multidisciplinary cooperation as the cornerstone of a favorable outcome.